Zur Eiparasitierung der Forleule Panolis flammea Schiffermüller (Lepidoptera, Noctuidae) in der Umgebung von Berlin im Jahre 1962. - Fankhänel, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1964)
During the propagation period 1961/1962 of Panolis flammea Schiffermüller studies were made in the pine area east of Berlin with a view of comparing the results of winter soil counts, later counts, and egg counts. First of all, however, the invasion of the eggs by Trichogramma parasites was examined. Larger egg sites of Panolis flammea showed higher percentages of eggs with parasites than short rows of eggs. In open area populations up to 30 per cent, of the eggs contained parasites. Experiments in which Trichogramma embryophagum Hartig was used under open area conditions (100000 animals per 250 square metres) brought only a very small increase, if any, in the percentages of parasites, because the natural parasite percentage was high anyway, and the experiments were undertaken too late. The paper also gives data about body dimensions of Trichogramma embryophagum which are connected with the number of parasites hatched from one moth egg and with the species of the host. The various breeds sometimes produced ichneumon flies of different forms.